Effect of phase composition on microstructure and wear resistance of (Al16.80Co20.74Cr20.49Fe21.28Ni20.70)99.5Ti0.5 high-entropy alloy coatings. (June 2022) - Cheng, Qiran; Shi, Haichuan; Jiang, Qi; Yu, Zhishui; Zhang, Peilei; Ye, Xin
Abstract: The (Al16.80 Co20.74 Cr20.49 Fe21.28 Ni20.70 )99.5 Ti0.5 high-entropy alloy coating was successfully prepared by laser cladding. The microstructure of the coating was controlled by changing the laser scanning speed, and three kinds of high-entropy alloy coatings with different microstructures were obtained. All coatings had an equiaxed grain structure, but the content of the BCC phase gradually increased with increasing laser scanning speed. In addition, the micro-mechanical properties of each phase in the coating and the creep characteristics of the coating were explored by the nanoindentation method. It was found that the BCC phase had greater hardness and elastic modulus than the FCC phase, so the content of the BCC phase dominated the hardness and wear resistance of the coating. At the same time, as the laser scanning speed increased, the creep resistance of the coating was gradually enhanced. When the laser scanning speed was 17 mm/s, the coating had the best wear resistance at room temperature and 500 ℃ high temperature. The main wear forms of the coating were abrasive wear, surface fatigue wear, and oxidative wear. Graphical Abstract: ga1